Spatio-temporal patterns of fish acoustic communities in Western Mediterranean coralligenous reefs: optimizing monitoring through recording duration - Gabriella La Manna; Mariangela Moro Merella; Riccardo Vargiu; Giuseppe Morello; Gianluca Sarà; Giulia Ceccherelli (Frontiers in Marine Science, 2024)
In this study, we explored the fish acoustic community at two coralligenous sites in Sardinia (Tavolara and Santa Teresa, western Mediterranean Sea) during the summer 2023. Our goal was to understand spatial and temporal patterns of fish acoustic activity on different temporal scales to offer insights for optimizing acoustic monitoring of this crucial ecosystem. We identified seventeen distinct sound types, revealing a diverse acoustic community. Tavolara had higher acoustic richness and abundance compared to Santa Teresa, which may be attributed to site-specific factors such as habitat structure, species composition, or levels of protection. Temporal analysis revealed clear diel patterns, with certain sounds associated with nocturnal or diurnal periods, reflecting the daily rhythms of different species. The study also examined how recording duration influenced acoustic richness, finding that longer recordings (15 minutes per hour and 15 minutes per hour at night) provided a more comprehensive detection of acoustic activity. Additionally, the number of recording days required to detect species richness varied depending on the site. While extended recordings improve the likelihood of detecting rare or sporadic sounds, they also present challenges in data management and equipment maintenance. The study underscores the importance of carefully planning sampling strategies to optimize acoustic monitoring and ensure effective and sustainable ecological research in coralligenous ecosystems.